Conservation value and ecosystem service provision of Nothofagus antarctica forests based on phenocluster categories - Martínez Pastur, Guillermo José; Rodríguez‑Souilla, Julián; Rosas, Yamina Micaela; Politi, Natalia; Rivera, Luis; Silveira, Eduarda M.O.; Olah, Ashley; Pidgeon, Anna Michle; Lencinas, María Vanessa; Peri, Pablo Luis (Springer Nature, 2025)
Traditional approaches of forest classifications were based on tree species composition, but recently combine phenology and climate to characterise functional (cyclic and seasonal greenness) rather than structural or compositional components (phenoclusters). The objective was to compare the conservation value (capacity to support more native biodiversity) and provision of ecosystem services (ES) in different phenocluster categories of Nothofagus antarctica forests in Tierra del Fuego (Argentina). We used available models (ES, potential biodiversity) and ground-truth data of 145 stands, comparing phenocluster values using uni- and multivariate analyses. Conservation value and capacity to supply ES significantly varied among phenocluster categories: (i) cultural, regulating, and provisioning ES and potential biodiversity at landscape level, (ii) soil carbon and nitrogen, (iii) dominant height, crown cover, basal area, total volume, and domestic animal stock, and (iv) understory plant richness and cover at stand level. These differences are linked to the forest capacity to support more native biodiversity and ES. Besides, multivariate analyses supporting the split of this forest type into four phenocluster subtypes (coast, highland, ecotone with other types, and degraded or secondary forests). Our findings suggest the needs of specific management and conservation proposals, based on phenoclusters rather than forest types defined by tree canopy-cover composition.